2004
DOI: 10.1111/j.1467-8489.2004.t01-1-00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk management strategies using seasonal climate forecasting in irrigated cotton production: a tale of stochastic dominance

Abstract: Decision‐making in agriculture is carried out in an uncertain environment with farmers often seeking information to reduce risk. As a result of the extreme variability of rainfall and stream‐flows in north‐eastern Australia, water supplies for irrigated agriculture are a limiting factor and a source of risk. The present study examined the use of seasonal climate forecasting (SCF) when calculating planting areas for irrigated cotton in the northern Murray Darling Basin. Results show that minimising risk by adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…This does not impair yields or the quality of the fiber. Tennakoon & Milroy (2003) and Ritchie et al (2004) obtained an increase in water use efficiency by studying some irrigation strategies, aiming at higher water saving.…”
Section: Introductionmentioning
confidence: 99%
“…This does not impair yields or the quality of the fiber. Tennakoon & Milroy (2003) and Ritchie et al (2004) obtained an increase in water use efficiency by studying some irrigation strategies, aiming at higher water saving.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, SDRF establishes necessary and sufficient conditions for the cumulative distribution function of F (y) to be preferred to the cumulative distribution function of G (y) by all individuals whose absolute risk aversion functions lie between lower r 1 (y) and upper bounds r 2 (y) (Harris and Mapp, 1986). Stochastic dominance with respect to a function has been implemented by many empirical studies (Barham et al, 2011;Cochran et al, 1985;Greene et al, 1985;Harris and Mapp, 1986;King and Robison, 1981;de la Llata et al, 1999;Musser et al, 1981;Parcell and Langemeier, 1997;Ritchie et al, 2004;Zacharias and Grube, 1984). It is a practical tool to help farmers better understand their risk preferences and choices under price, yield, or weather uncertainty (King and Robison, 1981).…”
Section: Stochastic Dominancementioning
confidence: 99%
“…This was achieved by coupling the ENSO/streamflow relationship with water allocation models used by water resource managers. Ritchie et al (2004) have combined economic, agronomic, hydrological and climatological modelling to assist with plant -area decisions for irrigated cotton farmers in the northern Murray-Darling Basin. Ritchie et al (2004) found that significant gains in gross margin returns can be obtained if farmers manage planting area based on seasonal climate forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al (2004) have combined economic, agronomic, hydrological and climatological modelling to assist with plant -area decisions for irrigated cotton farmers in the northern Murray-Darling Basin. Ritchie et al (2004) found that significant gains in gross margin returns can be obtained if farmers manage planting area based on seasonal climate forecasts. However, Ritchie et al (2004) also note that a farmer's response to seasonal climate forecasting is strongly influenced by attitude to risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation